Preclinical Evaluation of Long-Acting Emtricitabine Semi-Solid Prodrug Nanoparticle Formulations - Paul Curley; James J. Hobson; Neill J. Liptrott; Edward Makarov; Amer Al-khouja; Lee Tatham; Christopher A. W. David; Helen Box; Megan Neary; Joanne Sharp; Henry Pertinez; David Meyers; et al. (MDPI AG, 2023)
Long-acting injectable (LAI) formulations promise to deliver patient benefits by overcoming issues associated with non-adherence. A preclinical assessment of semi-solid prodrug nanoparticle (SSPN) LAI formulations of emtricitabine (FTC) is reported here. Pharmacokinetics over 28 days were assessed in Wistar rats, New Zealand white rabbits, and Balb/C mice following intramuscular injection. Two lead formulations were assessed for the prevention of an HIV infection in NSG-cmah−/− humanised mice to ensure antiviral activities were as anticipated according to the pharmacokinetics. Cmax was reached by 12, 48, and 24 h in rats, rabbits, and mice, respectively. Plasma concentrations were below the limit of detection (2 ng/mL) by 21 days in rats and rabbits, and 28 days in mice. Mice treated with SSPN formulations demonstrated undetectable viral loads (700 copies/mL detection limit), and HIV RNA remained undetectable 28 days post-infection in plasma, spleen, lung, and liver. The in vivo data presented here demonstrate that the combined prodrug/SSPN approach can provide a dramatically extended pharmacokinetic half-life across multiple preclinical species. Species differences in renal clearance of FTC mean that longer exposures are likely to be achievable in humans than in preclinical models.